A THE EFFECTIVENESS OF USE OF DIGITALIZATION IN SPEEDING THE DEVELOPMENT OF MSMEs IN GLOBAL ECONOMIC COMPETITION - Nelly Azwarni Sinaga; Yenni Sofiana Tambunan (SEAN Institute, 2022)
The existence of Micro, Small and Medium Enterprises (MSMEs) is an important highlight because of their sizeable share in the Indonesian economy. MSMEs are said to be the backbone of the Indonesian economy because they have a large contribution to Gross Domestic Product, absorb a high number of workers thereby reducing unemployment and poverty and encouraging increased investment and Indonesian exports. To strengthen the competitiveness of MSMEs, especially in global competition, MSMEs need to adapt and follow trends in technology, information and communication so as not to be left behind and stagnate. The problem raised in this research is how effective is the use of digitalization in spurring the development of MSMEs in global economic competition? This research method is library research based on literature related to research. The results of the discussion can identify many problems faced by MSMEs so that their growth and development are less than optimal. One of them is that there are still many MSMEs that are not yet digital-based in running their business, both in administrative management, HR, finance and marketing so that MSME products tend to be local. The solutions offered to accelerate the growth and development of MSMEs include the use of digitization in product management and marketing. So it can be concluded that digital-based MSMEs are effective in encouraging the growth and development of MSMEs. So it is suggested that MSMEs should take advantage of the digital system in running their business. Besides that, it is hoped that serious attention and government support for MSMEs through cross-sectoral policies. Key Word : Digitalization, MSMEs, Global Economic Competition